Grand Canal Innovation District A Vision for Ireland - Prendergast, Patrick; O'Brien, Diarmuid (Trinity College Dublin , the University of Dublin, 2018)
Trinity is spearheading the development of the Grand Canal Innovation District concept in collaboration with the other Dublin universities and the broader enterprise community. We are outlining our vision and issuing a call to action for industry, higher education, the local community, and government to collaborate on a new and critically important engine for the next phase of Ireland’s economic development. After 18 months of preparation, today we lay out how a globally competitive innovation district is achievable in Dublin. At a time when the availability of talent and innovation drives business investment and growth Dublin must play its role as a capital city for Ireland and establish the infrastructure necessary to compete internationally. A new innovation district, with a new university campus at its heart, will be a vital step in enabling Dublin to be ranked as a top 20 global city for innovation. It is achievable if we work together. We are not presenting a blueprint or a set of specific actions – that comes later. Today’s announcement by An Taoiseach Leo Varadkar sets down a marker that Ireland intends to play at the highest levels in the world’s innovation economy. The first step is providing a starting vision to enable an ecosystem-wide conversation on the challenges we face; the opportunities that are open to us and the choices that need to be made to ensure Ireland remains a globally competitive location for business, and becomes an internationally recognised hub for research and innovation. We encourage all stakeholders to participate, comment and provide feedback and support the development of an innovation district masterplan that is reflective of the entire ecosystem in the Grand Canal Dock area.
Keywords: Canal project